2022
DOI: 10.3329/bjnm.v25i1.59636
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Newborn Screening for the early Diagnosis of Congenital Hypothyroidism in Bangladesh

Abstract: Background: Newborn screening programs signify early and presymptomatic detection of treatable disorders which authorize commencement of prompt medication to alleviate notable fatality. Newborn screening (NBS) for congenital hypothyroidism (CH) has been a successful public health initiative in preventive medicine over the last few decades. Previous pilot (1999-2006) and phase 1 (2006-2011) NBS program in Bangladesh reported an increased incidence compared to global data which urged to initiate a second phase N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Bangladesh —The NBS movement for CH was introduced in Bangladesh in 1999 by Bangladesh Atomic Energy Commission (BAEC) and as a regional project of the IAEA. Studies from local pilots have demonstrated an occasionally effective program suitable for government support/management as part of a policy for combatting congenital diseases [ 431 ]. The screening laboratory at the Nuclear Medicine Institute at Bangabandhu Sheikh Mujib Medical University, Dhaka is a well-equipped NBS center under BAEC with 3–4 peripheral NBS centers (currently inactive).…”
Section: Resultsmentioning
confidence: 99%
“…Bangladesh —The NBS movement for CH was introduced in Bangladesh in 1999 by Bangladesh Atomic Energy Commission (BAEC) and as a regional project of the IAEA. Studies from local pilots have demonstrated an occasionally effective program suitable for government support/management as part of a policy for combatting congenital diseases [ 431 ]. The screening laboratory at the Nuclear Medicine Institute at Bangabandhu Sheikh Mujib Medical University, Dhaka is a well-equipped NBS center under BAEC with 3–4 peripheral NBS centers (currently inactive).…”
Section: Resultsmentioning
confidence: 99%
“…So routine newborn screening especially for CH should be started in our country. 2,[4][5][6] Incidence rates of ROP (Retinopathy of Prematurity) ranges from 10% to 46% among low birth weight premature infants. Studies from BSMMU and BSH&I showed incidence of ROP ranges from 24% to 35% in preterm infants.…”
Section: Mahbubul Hoquementioning
confidence: 99%